The Number of periodic solutions of a Riccati type logistic periodic equation - Fatah, K. S.; Amen2, A. I. (Sulaimani Journal for Pure and Applied Sciences, 2004)
In this paper, by using a simple transfomation of variables and the necessary and sufficient condition in order that a solution of a periodic equation be periodic it is proved that the periodic logistic equation (of Riccati type) has exactly two periodic solutions.
Keywords: A periodic equation no of solution of equation